2016
DOI: 10.1016/j.ram.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Sarcocystis aucheniae in the blood of llamas from Argentina

Abstract: Sarcocystis aucheniae are apicomplexan protozoa that infect South American camelids (SACs), giving rise to macroscopic cysts similar to rice grains in skeletal muscles. Visual detection of macrocysts in slaughtered animals hampers commercialization of SAC meat, a highly relevant economic exploitation for Andean rural families. Importantly, the consumption of undercooked S. aucheniae-infested meat causes gastroenteritis. A carnivore definitive host, possibly the dog, acquires the parasite when feeding on infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…A variety of molecular methods have been developed for assessing the genetic diversity as well as for the diagnosis of Sarcocystis spp. in animals [ 16 , 38 , 39 ]. The first molecular identification of macrocysts of S. aucheniae in alpacas was made in Australia where the 18S rRNA gene fragment was amplified using conventional polymerase chain reaction (PCR) [ 27 ], and the phylogenetic analyses of the 18S rRNA sequences revealed that these were different from those of Sarcocystis spp.…”
Section: Diagnosis Of Sarcocystosis In Sacsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of molecular methods have been developed for assessing the genetic diversity as well as for the diagnosis of Sarcocystis spp. in animals [ 16 , 38 , 39 ]. The first molecular identification of macrocysts of S. aucheniae in alpacas was made in Australia where the 18S rRNA gene fragment was amplified using conventional polymerase chain reaction (PCR) [ 27 ], and the phylogenetic analyses of the 18S rRNA sequences revealed that these were different from those of Sarcocystis spp.…”
Section: Diagnosis Of Sarcocystosis In Sacsmentioning
confidence: 99%
“…Contrarily, the detection of Sarcocystis DNA from body fluids (such as blood) could be a much more valuable diagnostic tool for early diagnosis, particularly for the identification of microcyst-forming Sarcocystis spp. Recently, a semi-nested PCR was developed to detect the DNA of S. aucheniae from blood in llamas [ 38 ]. This method allowed the detection of as few as 100 bradyzoites per ml of blood.…”
Section: Diagnosis Of Sarcocystosis In Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…El porcentaje, relativamente más bajo (74,0 %) hallados en alpacas de 2 años, se debe probablemente a que los quistes de Sarcocystis aff. aucheniae Brumpt, 1903(Carletti et al, 2013Martin et al, 2016;More et al, 2016) son de crecimiento lento y se hacen visibles entre 18 a 24 meses de edad (Leguía, 1991).…”
Section: Discussionunclassified
“…In a previous study, we showed for the first time that the transit of S. aucheniae through the SAC bloodstream can be detected by molecular methods (Martín et al., 2016). The present work was aimed at improving the molecular detection of S. aucheniae and applying it to llama samples of Argentina and Bolivia to estimate the field prevalence and risk factors, as well as studying the possible usefulness of this test for pre-slaughter diagnosis to predict the presence of cysts in llama meat.…”
Section: Introductionmentioning
confidence: 99%